Combined spinal-epidural analgesia in labour: its effects on delivery outcome - Singh,Suneet Kaur Sra Charanjit (2016)
ABSTRACT BACKGROUND AND OBJECTIVES: Combined spinal-epidural (CSE) has become an increasingly popular alternative to traditional labour epidural due to its rapid onset and reliable analgesia provided. This was a prospective, convenient sampling study to determine the effects of CSE analgesia on labour outcome. METHODS: One hundred and ten healthy primigravida parturients with a singleton pregnancy of ≥37 weeks gestation and in the active phase of labour were studied. They were enrolled to the CSE (n = 55) or Non-CSE (n = 55) group based on whether they consented to CSE analgesia. Non-CSE parturients were offered other methods of labour analgesia. The duration of the first and second stage of labour, rate of instrumental vaginal delivery and emergency cesarean section, and Apgar scores were compared. RESULTS: The mean duration of the first and second stage of labour was not significantly different between both groups. Instrumental delivery rates between the groups were not significantly different (CSE group, 11% versus Non-CSE group, 16%). The slightly higher incidence of cesarean section in the CSE group (16% versus 15% in the Non-CSE group) was not statistically significant. Neonatal outcome in terms of Apgar score of less than 7 at 1 and 5 min was similar in both groups. CONCLUSION: There were no significant differences in the duration of labour, rate of instrumental vaginal delivery and emergency cesarean section, and neonatal outcome in parturients who received compared to those who did not receive CSE for labour analgesia.